Product Knowledge and Product Quality on Purchase Decisions with Brand Trust as Intervening Variables in the Natural Silk & Lurik Tugu Mas Typical Weaving Business in Yogyakarta - Paksi, Faris Eka; Pranowo, Agus Setyo; Limakrisna, Nandan (Universitas Pakuan, 2023)
Research related to purchasing decisions shows that product knowledge, product quality and brand trust greatly influence purchasing decisions both directly and indirectly. The purpose of this research is to test and reveal empirically the factors that influence purchasing decisions, both direct factors, namely product knowledge and product quality, and indirect factors, namely brand trust. This research was conducted at Tenun Sutera Alam & Lurik Tugu Mas, Yogyakarta City and used quantitative data (from a questionnaire). The research sample consisted of 150 visitors who had purchased Tenun Sutera Alam & Lurik Tugu Mas products. SEM analysis is used to determine the effect between research variables. The results showed, 1) There is a positive and significant influence of product knowledge on purchasing decisions, 2) There is a positive and significant influence of product quality on purchasing decisions, 3) There is a positive and significant influence of brand trust on purchasing decisions, 4) There is a positive and significant influence product knowledge on brand trust, 5) There is a positive and significant influence of product quality on brand trust, 6) There is a positive and insignificant effect of product knowledge on purchasing decisions through brand trust and 7) There is a positive and insignificant influence of product quality on purchasing decisions through brand trust. This study proposes several strong indicator recommendations that have a high contribution to product knowledge, product quality and brand trust in order to improve purchasing decisions.